Effects of an itaconic acid comonomer on the structural evolution and thermal behaviors of polyacrylonitrile used for polyacrylonitrile‐based carbon fibers. Issue 19 (3rd May 2014) - Fu, Zhongyu; Gui, Yu; Liu, Shuang; Wang, Zhe; Liu, Baijun; Cao, Chunlei; Zhang, Huixuan
ABSTRACT The influence of an acid comonomer on the structural evolution and thermal behaviors of a polyacrylonitrile (PAN) terpolymer containing about 4.19 wt % methyl methacrylate and 0.98 wt % itaconic acid (IA) during a heating treatment were studied by Fourier transform infrared (FTIR) spectroscopy, differential scanning calorimetry (DSC), and thermogravimetry (TG) and compared with the PAN homopolymer. From the results of FTIR spectroscopy and DSC, we found that the presence of the IA comonomer promoted cyclization reactions at a faster rate and broadened the exothermic peak; this eased the concentration of heat release. By comparing the results of the TG data, we found that the presence of the IA comonomer promoted dehydrogenation reactions and the formation of a large quantity of better ladder structures. In additional, the better ladder structures that formed were easier to convert from ladder structures into graphitelike structures. The activation energy of random scissions at about 300°C was calculated by the Kissinger method. The results show that the presence of the IA comonomer inhibited the random scission reactions to some extent. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40834.